Effect of The Proportion of Tambaqui and Mung Beans on the Physicochemical and Organoleptic Characteristics of Nugget with the Addition of Carrageenan - Astiardi, Salma Meilla; Rosida (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
This study aims to determine the effect of the proportion of tambaqui and mung beans with the addition of carrageenan on the physicochemical and organoleptic characteristics of nuggets. In this study, nuggets were made from tambaqui due to its high protein and mineral content, along with mung beans, which are rich in vegetable protein and fiber. The experiment used a completely randomized design (CRD) with two factors and two replications. Factor 1 is the proportion of tambaqui and mung bean mash (90:10; 80:20; 70:30), and factor 2 is the addition of carrageenan (1%; 1.5%; 2%). The data obtained were analyzed statistically using ANOVA and followed by DMRT further tests at a significance level of 5%. The best results were showed that the treatment of the proportion of tambaqui and mung bean mash (70:30) and the addition of 1% carrageenan was the best treatment producing nuggets with physicochemical characteristics of chewiness 602.727 gf, water content 60.283%, ash content 1.196%, protein content 22.765%, fat content 6.573%, and organoleptic characteristics showed that each attribute had an average taste preference of 3.60 (slightly like), aroma 3.84 (slightly like), color 3.44 (slightly like), texture 2.92 (dislike), and overall appearance 3.68 (slightly like). SDG 2: Zero Hunger SDG 12: Responsible Consumption and ProductionSDG 14: Life Below Water